Tropospheric Ozone During the Last Interglacial. Issue 23 (1st December 2022) - Yan, Yuzhen; Banerjee, Asmita; Murray, Lee T.; Tie, Xin; Yeung, Laurence Y.
Abstract: The history of tropospheric O3, an important atmospheric oxidant, is poorly constrained because of uncertainties in its historical budget and a dearth of independent records. Here, we estimate the mean tropospheric O3 burden during the Last Interglacial period (LIG; 115 to 130 thousand years ago) using a record of the clumped isotopic composition of O2 (i.e., Δ36 values) preserved in Antarctic ice. The measured LIG Δ36 value is 0.03 ± 0.02‰ (95% CI) higher than the late pre‐industrial Holocene (PI; 1, 590–1, 850 CE) value and corresponds to a modeled 9% reduction in LIG tropospheric O3 burden (95% CI: 3%–15%), caused in part by a substantial reduction in biomass burning emissions during the LIG relative to the PI. These results are consistent with the hypothesis that late‐Pleistocene megafaunal extinctions caused woody and grassy fuels to accumulate on land, leading to enhanced biomass burning in the preindustrial Holocene. Plain Language Summary: When humans first began impacting the Earth's atmospheric chemistry is unclear because its "natural" state just prior to human intervention is not precisely known. Here, we reconstruct the history of an important atmospheric oxidant—tropospheric ozone—during the Last Interglacial period ∼127, 000 years ago when Earth's climate was similar to today but humans had not yet dispersed widely across the continents. We find that the Last Interglacial tropospheric ozone levels were lower than during the late 17th to 19th centuries by about 10%, most likely due to differing amounts of biomass burning. This result can be explained by a global increase in biomass burning after megafaunal grazers went extinct and caused woody and grassy fuels to accumulate on land. Key Points: Clumped isotopes of tropospheric oxygen are less abundant during the Last Interglacial than during the late pre‐industrial Holocene The clumped‐isotope data indicate less tropospheric ozone in the Last Interglacial than the pre‐industrial Holocene Larger pre‐industrial tropospheric ozone burden is compatible with elevated biomass burning after late‐Pleistocene megafaunal extinctions